2016
DOI: 10.17816/ov9315-21
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation syndrome and ocular adnexa

Abstract: Pseudoexfoliation syndrome (PEX) is a relatively widespread generalized age-related disease of connective tissue. It seems reasonable to evaluate the condition of ocular adnexa in patients with PEX. Purpose. To evaluate the condition of ocular adnexal tissue in PEX. Methods. 132 eyes of 66 patients with PEX syndrome and 128 eyes of 64 patients without it were enrolled in the prospective study. We evaluated function of upper eyelid levator muscle, lower eyelid retractors, horizontal lid laxity (HLL), canthal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…Furthermore, the tarsal attachments of the lower eyelid retractors may be weakened. On the other hand, PEX has not been associated with upper eyelid ptosis, possibly due to the fact that the upper eyelid retractors (levator palpebrae superioris, Muller's muscle) are comparatively stronger structures that are less likely to be affected by PEX fibrilopathy (38). Alteration in the anatomical stability of peri-ocular connective tissue elements complies with reports for similar extra-ocular changes, such as inguinal hernias ( 26) or pelvic organ prolapse in female patients (27).…”
Section: Tarsal and Canthal Tendon Involvementsupporting
confidence: 75%
See 3 more Smart Citations
“…Furthermore, the tarsal attachments of the lower eyelid retractors may be weakened. On the other hand, PEX has not been associated with upper eyelid ptosis, possibly due to the fact that the upper eyelid retractors (levator palpebrae superioris, Muller's muscle) are comparatively stronger structures that are less likely to be affected by PEX fibrilopathy (38). Alteration in the anatomical stability of peri-ocular connective tissue elements complies with reports for similar extra-ocular changes, such as inguinal hernias ( 26) or pelvic organ prolapse in female patients (27).…”
Section: Tarsal and Canthal Tendon Involvementsupporting
confidence: 75%
“…The accumulation of pseudoexfoliative material in the peri-ocular connective tissues includes the medial and lateral canthal tendons, tarsal plates and orbicularis oculi muscle (33,38). A study has reported that PEX may be associated with atonic changes of the orbicularis oculi and compromise the stability of medial and lateral canthal tendons, resulting in horizontal and vertical lid laxity and predisposing to the development of eyelid margin malpositions, such as entropion or ectropion (Fig.…”
Section: Tarsal and Canthal Tendon Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Пациенты с ПЭГ по сравнению с пациентами с ПОУГ имеет худший прогноз из-за более высоких колебаний уровня ВГД и более тяжелого поражения зрительного нерва [ 23] . Кроме того, у пациентов с ПЭГ отмечается более высокий процент неудач медикаментозного лечения (простагландины, бета-блокаторы, адреномиметики и ингибиторы карбоангидразы) по сравнению с пациентами с ПОУГ [24 ] . Заключение.…”
unclassified